An Alternative Site for Pin Placement in External Fixation of Pelvic Fractures: Lateral Posterior Pelvic External Fixator Surgical Technique - Russ, Matthias K.; Navarre, Pierre; Stevens, Jarrad P. (Frontiers in Surgery, 2021)
Introduction: The application of an external fixator for unstable pelvic fractures is an important component of many resuscitation protocols. Moreover, certain pelvic fractures may be treated with an external fixator without requiring further internal fixation. We report our initial clinical results with an alternate pelvic external fixator site, the lateral posterior external fixator (LPEF), and describe the surgical technique. Methods and materials: From 2010 to 2013, we identified 27 consecutive patients (mean age 46 years, range 18-80) treated by the same surgeon (blinded) with a LPEF in a level-1 trauma center. Retrospective data collection included mechanism of injury, surgical interventions and complications. Results: The LPEF was used in 16 patients as acute pelvic stabilization and converted at a median of 2 days (IQR 1-3.5) to internal fixation, whereas in 10 patients it was used as definitive treatment and removed at a median of 48 days (IQR 37-64). One patient deceased on day 14 secondary to his severe closed head injury. The only surgical complications were 2 wound infections (20%, 2/10 in the group of definitive LPEFs) which resolved without sequalae following the removal of the LPEF (at 36 and 50 days) and antibiotics, 1 case of loss of fixation leading to the removal of the LPEF at 71 days and 1 patient who had hypergranulating external fixator sites and eventually healed without any cutaneous sequalae. All fractures consolidated in good position. Discussion: The described techniques of pelvic external fixation include the anterosuperior (iliac wing), supra-acetabular (anteroinferior) and subcristal (anterior superior iliac spine) insertion sites. The reported infection rates in definitive pelvic fracture treatment range from 20% to 40%. Due to the localization of the insertion sites, the lateral femoral cutaneous nerve is potentially at risk with the last two techniques. On the other hand, the LPEF insertion site is quite safe as it is anatomically far from any nerves as well as the inguinal region, and allows easy access for laparotomy. The results in this series suggest that the lateral posterior pelvic external fixator technique is an alternative to previous techniques with a low risk of complications.